2022
DOI: 10.2478/auoc-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and pharmacokinetics studies of Curcuma longa (Curcumin) potency against Ebola virus

Abstract: The Ebola virus disease causing hemorrhagic fever in human, has been known for nearly about 40 years, with the most recent outbreak being in West Africa creating humanitarian crisis, where over 11,308 deaths were recorded as reported in 30th March, 2016 (World Health Organization). Till now, Ebola virus drugs have been far from achieving regulatory FDA approval, and coupled with toxicity of these drugs, it is become imperative to appraise the available trail drugs, as well as looking into alternative natural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The docking was performed with AutoDock Tool 1.5.6 and AutoDock Vina 1.1.2; proteins were treated; and molecular interactions between receptors and ligands were visualized with Edupymol version 1.7.4.4 and BIOVIA Discovery studio 2019, as previously reported. 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 The grid box using AutoDock tool before use of AutoDock Vina for docking calculations was as follows: center (X = 4.834, Y = 15.305, Z = 24.227) and size (X = 64, Y = 52, Z = 74) for 5ADH , and (X = 32.382, Y = 72.334, Z = 31.711) and size (X = 62, Y = 58, Z = 66) for 1RO6 , with default exhaustiveness (exhaustiveness = 8) for steady docking calculation speed.…”
Section: Resultsmentioning
confidence: 99%
“…The docking was performed with AutoDock Tool 1.5.6 and AutoDock Vina 1.1.2; proteins were treated; and molecular interactions between receptors and ligands were visualized with Edupymol version 1.7.4.4 and BIOVIA Discovery studio 2019, as previously reported. 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 The grid box using AutoDock tool before use of AutoDock Vina for docking calculations was as follows: center (X = 4.834, Y = 15.305, Z = 24.227) and size (X = 64, Y = 52, Z = 74) for 5ADH , and (X = 32.382, Y = 72.334, Z = 31.711) and size (X = 62, Y = 58, Z = 66) for 1RO6 , with default exhaustiveness (exhaustiveness = 8) for steady docking calculation speed.…”
Section: Resultsmentioning
confidence: 99%
“…Nano‐curcumin and curcumin nano‐emulsion reduce the viral replication of DENV‐1 and DENV‐2 due to potentially enhanced cell cytotoxicity and substance absorption (Nabila et al, 2020). Acceptable docking scores of curcumin against multiple targets of EBOV such as viral proteins (VP30, VP35, VP40, and VP24) have been documented (Adepoju et al, 2022; Setlur et al, 2017). It also has shown to decrease HTNV viral RNA levels in different organs of animal model (Wei et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on the effect of curcumin and/or curcuminoids against EBOV have been performed in silico. These in silico investigations have shown that curcumin has an acceptable docking score against multiple targets of EBOV such as viral proteins (VP30, VP35, VP40, and VP45) (Adepoju et al, 2022;Baikerikar, 2017;Setlur et al, 2017). An in vitro study on male rats receiving 125 μg/kg liposomal curcumin suggested strong evidence for the role of curcumin in IL-6 and TNF-α reduction (Helson et al, 2015).…”
Section: Ebola Virusmentioning
confidence: 99%
“…In year 2022, Semire et al proposed a computational study based on the antiviral activity of the phytochemicals of Curcuma longa against Ebola virus. [19] Similarly, Saeed et al, Widjaja et al, Malik et al and many more applied tools of CADD for designing antiviral against Ebola virus. [20][21][22][23] CADD is crucial in discovering new drugs against the Ebola virus (EBOV).…”
Section: Introductionmentioning
confidence: 99%
“…In year 2022, Semire et al. proposed a computational study based on the antiviral activity of the phytochemicals of Curcuma longa against Ebola virus [19] . Similarly, Saeed et al., Widjaja et al., Malik et al.…”
Section: Introductionmentioning
confidence: 99%